The Terms of Types, Principles, and Hierarchy of Abdi Dalem of Ngayogyakarta Hadiningrat Palace as the Identity of the Speaker - Ria Yuliati (Deskripsi Bahasa, 2022)
Language symbolizes the identity of the speakers, including the Javanese language used in Ngayogyakarta Hadiningrat Palace. Ngayogyakarta Palace as a speech community maintains its identity by continuing to use Javanese language in their terms and everyday language. Research on Javanese language in Ngayogyakarta Palace is very important to preserve the local language, as well as the identity of the speech community. One of the typical Javanese languages in the Palace is the terms about Abdi Dalem. This study aims to: 1) describe the types, principles, and hierarchies of Abdi Dalem of Ngayogyakarta Hadiningrat Palace, 2) describe the meaning of the terms of Abdi Dalem's types, principles, and hierarchies. This research is a qualitative research. The research data collection techniques are: 1) identification of research sites or individuals, 2) observation, , 3) literature study, 4) interviews5) audio or visual data collection. The data analysis techniques are 1) preparing data, 2) reading the data, 3) giving data code, 4) describing people/communities and categorizing themes, 5) representing descriptions and themes in qualitative narratives, 6) interpretating or giving the meaning of data. From the research that has been done based on gender, there are two kinds of Abdi Dalem of Ngayogyakarta Hadiningrat Palace, namely Abdi Dalem Kakung and Abdi Dalem Putri/Keparak. Based on their origin there are Abdi Dalem Punakawan Caos, Punakawan Tepas, and Abdi Dalem Kaprajan. The principles of Abdi Dalem of Ngayogyakarta Palace are nyawiji, greget, sengguh, ora mingkuh. The hierarchy of Abdi Dalem of Ngayogyakarta Palace from the lowest level is Jajar, Bekel Anom, Bekel Sepuh, Lurah, Penewu, Wedono, Riya Bupati, Bupati Anom, Bupati Sepuh, Bupati Kliwon, Bupati Nayoko, and Pangeran Sentana. The terms regarding the types, principles, and hierarchy of Abdi Dalem have their respective meanings. These terms use lexical typical Javanese language and not the Indonesian national language to preserve and maintain their social identity as a Javanese language-speaking community of residents of Ngayogyakarta Palace.